Multiphysics Stimulated Simulation Digital Twin Methods for Fleet Management (AIAA 2013-1578) - Reifsnider, Kenneth; Majumdar, Prasun (AAIA Conference Papers American Institute of Aeronautics and Astronautics, 2013)
This established annual conference provides a unique forum dedicated to the latest developments in the collective disciplines of structures, structural dynamics, and materials, adaptive structures, dynamics, gossamer systems, multidisciplinary design optimization, and non-deterministic approaches. A paper on Multiphysics Stimulated Simulation Digital Twin Methods for Fleet Management (AIAA 2013-1578) presented at the 2013 Structures Structural Dynamics and Materials and Co-located Conference.